GENOTYPE DIFFERENCE OF –572 G>C AND -174 G>C IL-6 GENE POLYMORPHISM BETWEEN BALINESE POSTMENOPAUSAL WOMEN WITH OSTEOPOROSIS AND WITHOUT OSTEOPOROSIS - Yulianto, E.; Astawa, P.; Siki-Kawiyana,; K. (BALI MEDICAL JOURNAL, 2013)
Background: Osteoporosis is a silent metabolic disease characterized by diminished bone mass and change in bone microstructure which cause increment of fracture risk. Until now, osteoporosis still becomes one of major health problems around the world. In Indonesia, the incidence of osteoporosis is 25%. Previous study have shown the relation between osteoporosis and IL-6 gene polymorphism at -572G>C and -174 G>C. There are some controversies about the correlation between these polymorphism and osteoporosis because of different result between each study. Genotype G polymorphism at -572 G>C of IL-6 gene has been correlated with lower Bone mineral density (BMD) and Genotype G polymorphism at -174G>C of IL-6 gene has been correlated with higher BMD value. In Indonesia, there are still no study about the association between IL-6 gene polymorphism and osteoporosis. In the future this IL-6 gene polymorphism could be used as a genetic marker for osteoporosis in postmenopausal woman. The objective of this study is to determine the difference of genotype of -572G>C and -174G>C polymorphism of IL-6 gene and osteoporosis in Balinese postmenopausal women. Method: This research design is a case control study. Sample was obtained at orthopedic outpatient clinic of Sanglah General Hospital, Bali-Indonesia from June 2012 until November 2012. The diagnosis of osteoporosis is described as BMD value with T score ? -2.5 SD using DEXA. All sample’s peripheral blood are taken to be isolated for DNA and analyzed for IL-6 gene polymorphism at -572G>C and -174G>C using Real Time PCR. Data obtained was analyzed with chi square test using SPSS. Results: This research found 11 osteoporosis sample from total 52 with no difference sample characteristic between case and control (p > 0.05). Using Chi square test, There was a significant differences between genotype -572 G>C; IL-6 gene polymorphism in Balinese postmenopausal woman with osteoporosis and in Balinese postmenopausal woman without osteoporosis (c2 = 41.85 and p = 0.001) and no significant differences between genotype -174 G>C;IL-6 polymorphism in Balinese postmenopausal woman with osteoporosis and in Balinese postmenopausal woman without osteoporosis(c2 = 0.283 and p = 0.518). This study discovered significant differences between genotype -572 G>C; IL-6 gene polymorphism in Balinese postmenopausal woman with osteoporosis and in Balinese postmenopausal woman without osteoporosis. Conclusion: We concluded that ethnic genetic profile variations affect the role of IL-6 gene polymorphism. In the future, this IL-6 gene polymorphism could be used as risk factor for osteoporosis in Balinese premenopausal woman